La cooperación de la biblioteca escolar y la pública: alfabetización en información, “biblioteca integrada” y el mundo virtual - MARZAL, Miguel Ángel; PARRA VALERO, Pablo (Revista General de Información y Documentación, 2009)
The stimuli of educative convergence between the school and public libraries are examined, within the framework of the new environments and educational models that the Society of the information is trying, a few stimuli tending to a model of cooperation more effective than till now existing. There is studied, then, the educational convergent process, based on the informative competitions on the electronic discourse, for major efficiency of the collaborative and lifelong learning in formal and non-formal education, in order to reach a convergent educative model, whose engine is the information literacy, phenomenon that transforms the educational role of the libraries, particularly the school and public, who find new ways of cooperation, as he is credited in different actions. Authors analyse, finally, two scenes of this partnership working between school and public libraries: the model joint-use, that is defined, describes its typology and their possibilities in future; the virtual world, Second Life and the MMORPGs, that are described, score their formative applications and their incorporation at libraries.